A REVIEW LITERATURE EMPLOYEE PERFORMANCE MODEL:LEADERSHIP STYLE, COMPENSATION AND WORK DISCIPLINE - Putra, Rio; lima Krisna, Nandan; Ali, Hapzi (Dinasti Publisher, 2021)
The purpose of this thesis is to study the influence of leadership style,compensation, work discipline, and employee performance. The method of writing scientific articles is by using qualitative methods and library research or library research. The results of this literature review article are: leadership syle has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance.